Accuracy of CT-navigated pedicle screw positioning in the cervical and upper thoracic region with and without prior anterior surgery and ventral plating. (October 2017) - Rienmüller, A.; Buchmann, N.; Kirschke, J. S.; Meyer, E. L.; Gempt, J.; Lehmberg, J.; Meyer, B.; Ryang, Y. M.
Abstract : Aims: We aimed to retrospectively assess the accuracy and safety of CT navigated pedicle screws and to compare accuracy in the cervical and thoracic spine (C2-T8) with (COMB) and without (POST) prior anterior surgery (anterior cervical discectomy or corpectomy and fusion with ventral plating: ACDF/ACCF). Patients and Methods: A total of 592 pedicle screws, which were used in 107 consecutively operated patients (210 COMB, 382 POST), were analysed. The accuracy of positioning was determined according to the classification of Gertzbein and Robbins on post-operative CT scans. Results: High accuracy was achieved in 524 screws (88.5%), 192 (87.7%) in the cervical spine and 332 (89%) in the thoracic spine, respectively. The results in the two surgical groups were compared and a logistic regression mixed model was performed to analyse the risk of low accuracy. Significantly lower accuracy was found in the COMB group with 82.9% versus 91.6% in the POST group (p = 0.036). There were no neurological complications, but two vertebral artery lesions were recorded. Three patients underwent revision surgery for malpositioning of a screw. Although the risk of malpositioning of a screw after primary anterior surgery was estimated to be 2.4-times higher than with posterior surgery alone, the overall rates of complication and revision were low. Conclusion: We therefore conclude that CT navigated pedicle screws can be positioned safely although greater caution must be taken in patients who have previously undergone anterior surgery. Cite this article: Bone Joint J 2017;99-B:1373–80.